Surrogate Model Considering Trim Condition for Design Optimization of High-Aspect-Ratio Flexible Wing - Im, Sunyoung; Kim, Euiyoung; Park, Kyunghyun; Lee, Dong-Ho; Chang, Seongmin; Cho, Maenghyo (International journal of aeronautical and space sciences, 2022)
An improved, bilevel surrogate model to optimize aerodynamic/nonlinear structural coupled problems, considering trim conditions, is proposed in this paper. The proposed model is applied to a high-aspect-ratio flexible wing. Computational fluid and structural dynamic codes are loosely coupled and interact with the coupling variables of pressure and displacement. Level 1 reduces the coupling variables, using proper orthogonal decomposition, enabling the expansion of any data field as a linear combination of several modes. Level 2 builds the surrogate model, considering proper orthogonal displacement coefficients and the angle of attack as input parameters and the pressure coefficients as output parameters. Unlike the conventional bilevel surrogate model, the improved bilevel surrogate model includes the angle of attack as an input parameter to facilitate the immediate calculation of the trim angle of attack. The wing model of Global Hawk is optimized using the improved bilevel surrogate model, and the conventional bilevel surrogate model was used to compare the results of design optimization under two conditions: including and excluding the trim condition.